Nonaqueous electrolyte secondary battery
By attaching sulfonic acid compounds to the positive electrode active substance of the nonaqueous electrolyte secondary battery and using a specific silicon-containing material on the negative electrode, the problem of difficulty in achieving high capacity and high charge and discharge efficiency at the same time in the prior art is solved, and efficient battery performance is achieved.
Patent Information
- Application Number
- CN202380059884.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-20
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve high capacity and high charge and discharge efficiency in a nonaqueous electrolyte secondary battery at the same time, especially because the charge and discharge efficiency of the negative electrode has a great impact on the overall battery efficiency due to the reduction of the reaction resistance.
By attaching a sulfonic acid compound to the surface of the lithium-containing transition metal composite oxide particles of the positive electrode active material, and using a carbon-containing material and a silicon-containing material as the active material in the negative electrode, the content of the silicon-containing material is controlled to be 3 mass% or less of the total mass of the negative electrode active material.
A nonaqueous electrolyte secondary battery that takes into account both high capacity and high charge and discharge efficiency is realized. By reducing the reaction resistance of the positive electrode and suppressing the irreversible reaction of the negative electrode, the charging and discharge depth and efficiency of the overall battery are improved.
Smart Images

Figure CN119731822A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Patent document 1 proposes that Li4Ti5O 12 An active material having a surface layer composed of a lithium sulfonate compound formed on the surface of lithium titanate particles as a main component. Patent Document 1 states that by using this active material in a negative electrode active material, a change in resistance of a battery before and after charge storage can be suppressed.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0006] In non-aqueous electrolyte secondary batteries, it is an important issue to improve the charge and discharge efficiency while ensuring high capacity. The prior art including Patent Document 1 cannot fully address such issues, and there is still much room for improvement.
[0007] The non-aqueous electrolyte secondary battery disclosed herein is characterized in that it comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, the positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, the sulfonic acid compound being a compound represented by formula (I), and the negative electrode comprises a carbon material and a silicon-containing material as negative electrode active materials, and the content of the silicon-containing material is less than 3% by mass of the total mass of the negative electrode active material.
[0008]
[0009] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0010] The nonaqueous electrolyte secondary battery disclosed herein has a high capacity and is excellent in charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. DETAILED DESCRIPTION
[0012] The research results of the present inventors and others have made it clear that by having a sulfonic acid compound shown in the above formula (I) on the surface of the particles of the lithium-containing transition metal composite oxide used as the positive electrode active material, a high-capacity non-aqueous electrolyte secondary battery can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, it has been confirmed that as the charge and discharge depth deepens due to the reduction of the reaction resistance, the charge and discharge efficiency of the negative electrode has a greater impact on the charge and discharge efficiency of the non-aqueous electrolyte secondary battery as a whole. It is believed that the reason is that as the reaction resistance in the positive electrode is reduced due to the function of the sulfonic acid compound, the charge and discharge depth becomes deeper, and the capacity of the positive electrode becomes greater than the capacity of the negative electrode, becoming a negative electrode limitation. When charge and discharge become negative electrode limitations, the charge and discharge efficiency of the negative electrode has a greater impact on the charge and discharge efficiency of the non-aqueous electrolyte secondary battery as a whole, so even if the sulfonic acid compound is used for the positive electrode to make the positive electrode more efficient, the improvement of the charge and discharge efficiency of the non-aqueous electrolyte secondary battery as a whole is limited.
[0013] As described above, when the sulfonic acid compound is applied to the surface of particles of the lithium-containing transition metal composite oxide, it specifically functions to reduce the reaction resistance in the positive electrode and deepen the charge and discharge depth of the positive electrode. However, when the sulfonic acid compound is simply applied to the positive electrode, the charge and discharge are easily restricted by the negative electrode, making it difficult to achieve a non-aqueous electrolyte secondary battery with high charge and discharge efficiency.
[0014] Therefore, the inventors of the present invention have further repeatedly studied and successfully improved the overall charge and discharge efficiency of the non-aqueous electrolyte secondary battery by using a negative electrode active material with high charge and discharge efficiency at the negative electrode. Specifically, a lithium-containing transition metal composite oxide with a specific sulfonic acid compound attached to the surface of the particles is used as a positive electrode active material, and a negative electrode active material containing a carbon material and a silicon-containing material, and the content of the silicon-containing material is less than 3% by mass of the total mass of the negative electrode active material is used for the negative electrode. When the silicon-containing material is used for the negative electrode active material, Si undergoes an irreversible reaction during charging and discharging and becomes Li4SiO4, etc., thereby reducing the charge and discharge efficiency of the negative electrode. By setting the content of the silicon-containing material to less than 3% by mass of the total mass of the negative electrode active material, the above-mentioned irreversible reaction can be suppressed and the charge and discharge efficiency of the negative electrode can be improved. Thus, a non-aqueous electrolyte secondary battery that takes into account the high capacity and high charge and discharge efficiency brought about by the application of sulfonic acid compounds to the positive electrode can be realized.
[0015] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail with reference to the drawings. It should be noted that a configuration obtained by selectively combining the various configuration features of the multiple embodiments and modifications described below is included in the scope of the present disclosure.
[0016] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0017] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is referred to as the upper side, and the bottom side of the outer can 16 is referred to as the lower side.
[0018] The non-aqueous electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.
[0019] Liquid electrolyte (electrolyte) comprises non-aqueous solvent and electrolyte salt dissolved in non-aqueous solvent. Non-aqueous solvents include, for example, esters, ethers, nitriles, amides, and mixed solvents of more than two of these. As an example of non-aqueous solvents, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof can be cited. Non-aqueous solvents can also contain halogen substitution bodies (for example, fluoroethylene carbonate, etc.) in which at least a portion of hydrogen in these solvents is replaced by halogen atoms such as fluorine. Lithium salts such as LiPF6 are used in electrolyte salts.
[0020] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in a fully solid lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt, and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As a polymer material, fluororesins, acrylic resins, polyether resins, etc. can be listed.
[0021] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by spiral winding. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0022] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0023] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the open end of the outer can 16 that is pressed and connected to the sealing body 17.
[0024] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , in particular, the positive electrode active material constituting the positive electrode 11 and the negative electrode active material constituting the negative electrode 12 will be described in detail.
[0026] [positive electrode]
[0027] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, etc. The positive electrode mixture layer 31 preferably contains a positive electrode active material, a conductive agent, and a binder, and is disposed on both sides of the positive electrode core 30 except for the portion to which the positive electrode lead 20 is connected. The positive electrode 11 is manufactured, for example, in the following manner: The positive electrode 11 is manufactured, for example, in the following manner: A positive electrode composite material slurry containing a positive electrode active material, a conductive agent, and a binder is applied to the surface of the positive electrode core 30, and after the coating is dried, it is compressed to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30, thereby being manufactured.
[0028] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1 to 5.0% by mass relative to the mass of the positive electrode mixture layer 31.
[0029] The positive electrode 11 includes a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing transition metal composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).
[0030]
[0031] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0032] The sulfonic acid compound represented by formula (I) (hereinafter, sometimes referred to as "sulfonic acid compound") reduces the reaction resistance in the positive electrode 11 and improves the power characteristics of the battery. In addition, as the resistance is reduced, the charge and discharge depth can be deepened, and high capacity can be achieved. The sulfonic acid compound can exert this effect even in a very small amount, but it is preferably present on the particle surface of the composite oxide in an amount of 0.01% by mass or more relative to the mass of the lithium-containing transition metal composite oxide. The content of the sulfonic acid compound is more preferably 0.05% by mass or more, and particularly preferably 0.10% by mass or more relative to the mass of the lithium-containing transition metal composite oxide.
[0033] The upper limit of the content of the sulfonic acid compound is not particularly limited, but is preferably 2.0% by mass, more preferably 1.5% by mass, and particularly preferably 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide from the viewpoint of the cycle characteristics of the nonaqueous electrolyte secondary battery 10. The sulfonic acid compound is present, for example, in an amount of 0.05 to 1.50% by mass or 0.1 to 1.0% by mass relative to the mass of the lithium-containing transition metal composite oxide.
[0034] The positive electrode active material has a lithium-containing transition metal composite oxide with a sulfonic acid compound attached to the particle surface, that is, a composite particle as a main component, or can be substantially composed of only the composite particle. It should be noted that, within the scope of not impairing the purpose of the present disclosure, the positive electrode active material may also contain a composite oxide or other compound other than the composite particle.
[0035] The lithium-containing transition metal oxide preferably has a layered rock salt structure. As the layered rock salt structure of the lithium-containing transition metal oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing transition metal oxide comprises a transition metal layer, a Li layer and an oxygen layer.
[0036] The lithium-containing transition metal oxide is a composite oxide containing metal elements such as Co, Mn, Ni, and Al in addition to Li. The metal element constituting the lithium-containing transition metal oxide is, for example, at least one selected from Mg, Al, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Y, Zr, Sn, Sb, W, Pb, and Bi. Among them, it is preferred to contain at least one selected from Co, Ni, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Mn and a composite oxide containing Ni, Co, and Al can be listed.
[0037] From the viewpoint of high capacity, the lithium-containing transition metal oxide preferably contains 70 mol% or more, more preferably 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing transition metal oxide with a high Ni content is used. The Ni content relative to the total molar number of metal elements other than Li can be 85 mol% or more, or 90 mol% or more. The upper limit of the Ni content is, for example, 95 mol%.
[0038] As described above, an example of a suitable lithium-containing transition metal oxide is a composite oxide containing Ni, Co, and Al. Relative to the total molar number of metal elements other than Li, the content of Al is 4 to 15 mol%, and the content of Co is less than 1.5 mol%. If the content of Al is within this range, it helps to stabilize the crystal structure and improve the cycle characteristics. Co may not be substantially added, and the battery performance is improved by adding a small amount of Co.
[0039] Lithium-containing transition metal oxides are, for example, of the general formula Li a Ni x Al y Co z M1 w O 2-b (wherein, 0.8≤a≤1.2, 0.85≤x≤0.95, 0.04≤y≤0.15, 0≤z≤0.015, 0≤w≤0.15, 0≤b<0.05, x+y+z+w=1, M1 is at least one element selected from the group consisting of Mn, Fe, Ti, Si, Nb, Zr, Mo and Zn.) A composite oxide represented by M1 is preferably Mn.
[0040] The content of elements constituting the lithium-containing transition metal composite oxide can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0041] The lithium-containing transition metal composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, it is 3 μm to 30 μm, preferably 5 μm to 25 μm. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Inc., MT3000II) and water as the dispersion medium.
[0042] The average particle size of primary particles constituting the lithium-containing transition metal composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles obtained by analyzing a scanning electron microscope (SEM) image of a cross section of secondary particles.
[0043] The sulfonic acid compound present on the surface of the particles of the lithium-containing transition metal composite oxide is a compound represented by formula (I) as described above.
[0044]
[0045] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.
[0046] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, and more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of hydrogen bonded to carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.
[0047] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.
[0048] The sulfonic acid compound is, for example, uniformly present on the entire surface of the particles of the lithium-containing transition metal composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the lithium-containing transition metal composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.
[0049] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the particle surface of the lithium-containing transition metal composite oxide can also be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.
[0050] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.
[0051] First, a metal oxide containing metal elements such as Ni, Al, Co, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing transition metal composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Al, Co, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing metal elements such as Ni, Al, Co, and Mn, and heat-treating the composite hydroxide to enable synthesis. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.
[0052] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.
[0053] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture may also be calcined through multiple temperature rising processes. The calcining process may include, for example, the following steps: a first temperature rising process of heating to 450°C to 680°C at a temperature rising rate of 1.0°C / min to 5.5°C / min; and a second temperature rising process of heating to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min to 3.5°C / min. The maximum reaching temperature of the calcining process may be set to 700°C to 850°C, and may be maintained at this temperature for 1 hour to 10 hours.
[0054] Next, the calcined product (lithium-containing transition metal composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out using existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can also be carried out under a vacuum atmosphere. An example of drying conditions is at a temperature of 150°C to 400°C for 0.5 hours to 15 hours.
[0055] The sulfonic acid compound is added, for example, to the cake-like composition obtained in the washing step or the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing transition metal composite oxide can be obtained. The sulfonic acid compound may also be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass to 40% by mass.
[0056] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding a sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.
[0057] [negative electrode]
[0058] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the surface of the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 preferably includes a negative electrode active material and a binder, and is disposed on both surfaces of the negative electrode core 40 except for a portion to which the negative electrode lead 21 is connected. The negative electrode 12 may be manufactured, for example, by applying a negative electrode mixture slurry including a negative electrode active material and a binder to the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layers 41 on both surfaces of the negative electrode core 40.
[0059] The binder contained in the negative electrode mixture layer 41 may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt. The content of the binder is, for example, 0.1 to 5% by mass relative to the mass of the negative electrode mixture layer 41. It should be noted that the negative electrode mixture layer 41 may also contain a conductive agent such as CNT.
[0060] The negative electrode 12 includes a carbon material and a silicon-containing material as negative electrode active materials. By using a carbon material and a silicon-containing material in combination, a high capacity can be achieved. In addition, the negative electrode 12, for example, substantially only includes a carbon material and a silicon-containing material as negative electrode active materials. It should be noted that in the non-aqueous electrolyte secondary battery 10 using the positive electrode 11 using a sulfonic acid compound, there is a tendency for the cycle characteristics to be reduced in the absence of a silicon-containing material.
[0061] The content of the silicon-containing material is 3% by mass or less of the total mass of the negative electrode active material. When the content of the silicon-containing material is greater than 3% by mass of the total mass of the negative electrode active material, Si undergoes an irreversible reaction during charge and discharge and is easily converted into Li4SiO4 or the like, thereby reducing the charge and discharge efficiency of the negative electrode 12. When the charge and discharge efficiency of the negative electrode 12 is reduced, it is difficult to improve the overall charge and discharge efficiency of the nonaqueous electrolyte secondary battery 10 even when the sulfonic acid compound is used for the positive electrode 11.
[0062] From the viewpoint of improving the charge and discharge efficiency, the content of the silicon-containing material is 3% by mass or less of the total mass of the negative electrode active material. When the content of the silicon-containing material is too low, the cycle characteristics of the non-aqueous electrolyte secondary battery 10 tend to decrease. Therefore, the content of the silicon-containing material is preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. Therefore, an example of a suitable range of the content of the silicon-containing material is 0.3 to 3% by mass of the total mass of the negative electrode active material. In the case of paying special attention to the cycle characteristics, the content of the silicon-containing material can also be 0.5 to 3% by mass.
[0063] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof are preferably used. The volume-based D50 of the carbon material is, for example, 1 μm to 30 μm, preferably 5 μm to 25 μm.
[0064] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) plane spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called graphitizable carbon, which is carbon that is easily graphitized by high temperature treatment compared to hard carbon. Hard carbon is also called difficult to graphitize carbon. It should be noted that in the composition of the present invention, there is no need to clearly distinguish between soft carbon and hard carbon. As a negative electrode active material, graphite and at least one amorphous carbon of soft carbon and hard carbon can also be used in combination.
[0065] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds, and composite materials containing Si can be cited. Among them, composite materials containing Si are preferred. The D50 of the composite material is usually smaller than the D50 of graphite. The volume-based D50 of the composite material is, for example, 1 μm to 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.
[0066] Suitable silicon-containing materials (composite materials) are composite particles containing an ion-conductive phase, an Si phase dispersed in the ion-conductive phase, and a conductive layer covering the surface of the ion-conductive phase. The ion-conductive phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silica phase. The ion-conductive phase is a continuous phase composed of a collection of finer particles than the Si phase. The silicide phase is a phase of a compound formed by Si and an element more electropositive than Si. As an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si in the form of fine particles. The conductive layer is composed of a material having a higher conductivity than the ion-conductive layer and forms a good conduction path in the negative electrode mixture layer 41.
[0067] An example of a suitable composite material containing Si is a composite particle having a sea-island structure in which Si is dispersed substantially uniformly in an amorphous silica phase in a particulate form and having a general formula SiO x (0 < x ≤ 2). The main component of the silica can also be silicon dioxide. The content ratio (x) of oxygen to Si is, for example, 0.5 ≤ x < 2.0, preferably 0.8 ≤ x ≤ 1.5.
[0068] Another example of a suitable composite material containing Si is a composite particle having a sea-island structure in which Si is dispersed substantially uniformly in an ion-conductive phase in a particulate form. The ion-conductive phase contains, for example, at least one selected from the group consisting of an alkali metal element and a Group II element. Further, the ion-conductive phase can also contain other elements M other than the alkali metal element and the Group II element. The element M can also be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F, W, and lanthanide elements.
[0069] A suitable ion-conductive phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a phase of a composite oxide represented by the general formula Li 2z SiO (2+z) (0 < z < 2). It is preferred that Li4SiO4 (Z = 2) is not contained in the lithium silicate phase. Li4SiO4 is an unstable compound and reacts with water to show alkalinity. Therefore, it sometimes deteriorates Si and causes a reduction in the charge-discharge capacity. From the viewpoints of stability, productivity, Li ion conductivity, etc., the lithium silicate phase is preferably mainly composed of Li2SiO3 (Z = 1) or Li2Si2O5 (Z = 1 / 2).
[0070] Another example of a suitable composite material containing Si is a composite particle having a sea-island structure in which fine Si is roughly uniformly dispersed in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may also contain a crystalline phase component, but preferably has more amorphous phase components. The amorphous carbon phase is composed of, for example, a carbon material having an average interplanar spacing of more than 0.34 nm in the (002) plane measured by X-ray diffraction. The amorphous carbon phase is composed of, for example, particles of amorphous carbon. It should be noted that the composite material containing the carbon phase may have a conductive layer different from the carbon phase, or may not have the conductive layer.
[0071] The conductive layer formed on the surface of the composite material particles is, for example, a carbon coating composed of a conductive carbon material. Carbon black such as acetylene black and Ketjen black, graphite, amorphous carbon (amorphous carbon) with low crystallinity, etc. can be used as the conductive carbon material. Considering the conductivity and the diffusion of Li ions into the interior of the particles, the thickness of the conductive layer is preferably 1nm to 200nm or 5nm to 100nm. The thickness of the conductive layer can be measured by cross-sectional observation of the composite material using SEM or transmission electron microscopy (TEM).
[0072] [Separator]
[0073] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.
[0074] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0075] In the non-aqueous electrolyte secondary battery 10 according to the present embodiment, after discharging until the battery voltage reaches 2.50 V, the open circuit voltage of the positive electrode 11 is preferably lower than 3.555 V (vs. Li / Li+). The open circuit voltage of the positive electrode 11 can be obtained by disassembling a battery cell discharged at a current rate of 0.01C until the voltage reaches 2.50 V and measuring the positive electrode 11 using lithium metal as a counter electrode.
[0076] Example
[0077] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0078] <Example 1>
[0079] [Preparation of positive electrode active material]
[0080] The coprecipitation method was used to obtain [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain a metal oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the above metal oxides were mixed in such a way that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was heated under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture is calcined from room temperature to 650°C at a heating rate of 2.0°C / min and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a lithium-containing composite oxide (synthesis process). Water is added to the lithium-containing composite oxide in a slurry concentration of 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition (cleaning process). Powdered lithium methanesulfonate is added to the cake-like composition (addition process). The amount of lithium methanesulfonate added is 0.1% by mass relative to the total mass of the lithium-containing composite oxide. After the addition process, a drying process is performed under vacuum atmosphere at 180°C for 2 hours to obtain the positive electrode active material of Example 1. It should be noted that the presence of lithium sulfonate on the surface of the positive electrode active material was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0081] [Production of positive electrode]
[0082] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, the coating is dried, and after compression, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0083] [Production of negative electrode]
[0084] Artificial graphite and SiO2 were mixed in a mass ratio of 99.2:0.8. x(0 < x ≤ 2) is used as the negative electrode active material. A dispersant is prepared by mixing the negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) at a solid component mass ratio of 100:1:1, and water is used as the dispersion medium to prepare the negative electrode mixture paste. The negative electrode mixture paste is coated on both sides of a negative electrode core made of a copper foil. After the coating film is dried, the coating film is calendered using a roller and cut into a specified electrode size to obtain a negative electrode with a negative electrode mixture layer formed on both sides of the negative electrode core. In addition, an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode. It should be noted that in a battery made with this negative electrode as the working electrode and metallic lithium as the counter electrode, the initial charge-discharge efficiency of the negative electrode is obtained from the ratio of the discharge capacity when discharging at a constant current rate of 0.1C until 0.0V to the charge capacity when charging at a constant current rate of 0.1C until 1.0V after discharging at a constant current rate of 0.1C until 0.0V. As a result, the initial charge-discharge efficiency of the negative electrode in Example 1 is 94%.
[0085] [Preparation of Non-aqueous Electrolyte]
[0086] A non-aqueous electrolyte is prepared by dissolving LiPF6 at a concentration of 1.2 mol / L in a mixed solvent obtained by mixing ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) at a volume ratio of 3:3:4 (at 25°C).
[0087] [Fabrication of Test Battery Cell (Non-aqueous Electrolyte Secondary Battery)]
[0088] Aluminum leads are respectively installed at the exposed portions of the above-mentioned positive electrode, and nickel leads are installed at the exposed portions of the above-mentioned negative electrode. The positive electrode and the negative electrode are wound into a spiral shape隔着 a separator made of polyolefin to fabricate a wound electrode body. The electrode body is housed in an outer can made of an aluminum laminate, and after injecting the above-mentioned non-aqueous electrolyte, the opening of the outer can is sealed to obtain a test battery cell.
[0089] [Measurement of Charge-discharge Efficiency]
[0090] For the above-mentioned test battery cell, at an ambient temperature of 25°C, it is discharged at a constant current of 0.2It until 2.5V. Then, it is charged at a constant current of 0.2It until 4.2V, and the charge capacity at this time is taken as A. Then, it is charged at a constant voltage of 4.2V until 0.02It, and the charge capacity at this time is taken as B. Further, it is discharged at a constant current of 0.2It until 2.5V, and the discharge capacity at this time is taken as C. In addition, the charge-discharge efficiency is taken as C / (A + B) for evaluation.
[0091] [Measurement of Open-circuit Voltage of Positive Electrode]
[0092] For the above test battery cells, constant current discharge was carried out at a current rate of 0.01C until the battery voltage became 2.5V, and then the test battery cells were disassembled. For the positive electrode, lithium metal was used as the counter electrode, and the open circuit voltage was evaluated. The open circuit voltage of the positive electrode of the test battery cell of Example 1 was 3.544V.
[0093] <Example 2>
[0094] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.3% by mass, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0095] <Example 3>
[0096] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0097] <Example 4>
[0098] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 1.0% by mass, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0099] <Example 5>
[0100] In the step of adding the positive electrode active material, sodium methanesulfonate was added as a sulfonic acid compound, and its addition amount relative to the total mass of the lithium-containing composite oxide was 0.5% by mass. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0101] <Example 6>
[0102] In the step of adding the positive electrode active material, lithium ethanesulfonate was added as a sulfonic acid compound, and its addition amount relative to the total mass of the lithium-containing composite oxide was 0.5% by mass. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0103] <Example 7>
[0104] In the step of adding the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5% by mass. In the production of the negative electrode, artificial graphite and SiOx (0 < x ≤ 2) were mixed at a mass ratio of 97.0:3.0. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0105] <Comparative Example 1>
[0106] In the addition step of the positive electrode active material, a sulfonic acid compound was not added, and a test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0107] <Comparative Example 2>
[0108] In the addition step of the positive electrode active material, lithium succinate was added, and the addition amount thereof was 0.5% by mass based on the total mass of the lithium-containing composite oxide. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0109] <Comparative Example 3>
[0110] In the addition step of the positive electrode active material, lithium oxalate was added, and the addition amount thereof was 0.5% by mass based on the total mass of the lithium-containing composite oxide. A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0111] <Comparative Example 4>
[0112] In the addition step of the positive electrode active material, a sulfonic acid compound was not added. In the production of the negative electrode, artificial graphite and SiO were mixed at a mass ratio of 97.0:3.0 x (0 < x ≤ 2). A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0113] <Comparative Example 5>
[0114] In the addition step of the positive electrode active material, the addition amount of lithium methanesulfonate based on the total mass of the lithium-containing composite oxide was set to 0.5% by mass. In the production of the negative electrode, artificial graphite and SiO were mixed at a mass ratio of 96.2:3.8 x (0 < x ≤ 2). A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0115] <Comparative Example 6>
[0116] In the addition step of the positive electrode active material, a sulfonic acid compound was not added. In the production of the negative electrode, artificial graphite and SiO were mixed at a mass ratio of 96.2:3.8 x (0 < x ≤ 2). A test battery cell was produced in the same manner as in Example 1 except for this, and evaluation was carried out.
[0117] The charge and discharge efficiency, the open circuit voltage of the positive electrode, and the initial charge and discharge efficiency of the negative electrode of the test battery cells of the embodiment and the comparative example are shown in Table 1, Table 2, and Table 3, respectively. It should be noted that the charge and discharge efficiency in Table 1 is a relative value when the charge and discharge efficiency of the test battery cell of Comparative Example 1 is set to 100, the charge and discharge efficiency in Table 2 is a relative value when the charge and discharge efficiency of the test battery cell of Comparative Example 4 is set to 100, and the charge and discharge efficiency in Table 3 is a relative value when the charge and discharge efficiency of the test battery cell of Comparative Example 6 is set to 100. A larger value indicates a better charge and discharge efficiency.
[0118] [Table 1]
[0119]
[0120] [Table 2]
[0121]
[0122] [Table 3]
[0123]
[0124] As shown in Table 1, the test cells of Examples 1 to 6, in which a sulfonic acid compound was used in the positive electrode and a negative electrode active material with a silicon content of 0.8% by mass was used in the negative electrode, showed improved charge and discharge efficiency compared with the test cell of Comparative Example 1, in which no sulfonic acid compound was used in the positive electrode and a negative electrode active material with a silicon content of 0.8% by mass was used in the negative electrode. In addition, the test cells of Comparative Examples 2 and 3, in which lithium succinate or lithium oxalate was used in the positive electrode and a negative electrode active material with a silicon content of 0.8% by mass was used in the negative electrode, showed deteriorated charge and discharge efficiency compared with the test cell of Comparative Example 1. In addition, as shown in Table 2, in the case of using a negative electrode active material with a silicon content of 3.0% by mass in the negative electrode, the charge and discharge efficiency was also improved by using a sulfonic acid compound in the positive electrode.
[0125] As shown in Table 3, the test battery cell of Comparative Example 5, in which a sulfonic acid compound is used in the positive electrode and a negative electrode active material with a silicon content of 3.8 mass % is used in the negative electrode, and the test battery cell of Comparative Example 6, in which no sulfonic acid compound is used in the positive electrode and a negative electrode active material with a silicon content of 3.8 mass % is used in the negative electrode, has equivalent charge and discharge efficiency.
[0126] From the above results, when a negative electrode active material having a silicon content of 3% or less of the total mass of the negative electrode active material is used in the negative electrode, the charge-discharge efficiency is greatly improved by using a sulfonic acid compound in the positive electrode. On the other hand, when a negative electrode active material having a silicon content of more than 3% of the total mass of the negative electrode active material is used in the negative electrode, the improvement in charge-discharge efficiency is limited even if a sulfonic acid compound is used in the positive electrode.
[0127] The present disclosure is further described through the following embodiments.
[0128] Configuration 1: A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of particles of the composite oxide, wherein the sulfonic acid compound is a compound represented by the above formula (I), and the negative electrode comprises a carbon material and a silicon-containing material as negative electrode active materials, wherein the content of the silicon-containing material is less than 3% by mass of the total mass of the negative electrode active material.
[0129] Configuration 2: The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.
[0130] Configuration 3: The nonaqueous electrolyte secondary battery according to Configuration 1 or 2, wherein A in the above formula (I) is Li or Na.
[0131] Configuration 4: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R in the formula (I) is an alkyl group having 3 or less carbon atoms.
[0132] Configuration 5: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the lithium-containing transition metal composite oxide has a layered rock salt structure.
[0133] Configuration 6: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the negative electrode has an initial charge and discharge efficiency of 90% or more.
[0134] Configuration 7: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the open circuit voltage of the positive electrode after discharging until the battery voltage reaches 2.5 V is lower than 3.555 V (vs. Li / Li+).
[0135] Configuration 8: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0136] Configuration 9: The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the silicon-containing material includes an ion conductive phase, a Si phase dispersed in the ion conductive phase, and a conductive layer covering a surface of the ion conductive phase.
[0137] Configuration 10: The nonaqueous electrolyte secondary battery according to Configuration 9, wherein the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
[0138] Configuration 11: The nonaqueous electrolyte secondary battery according to Configuration 9 or 10, wherein the ion conductive phase contains at least one selected from the group consisting of alkali metal elements and Group II elements.
[0139] Configuration 12: A non-aqueous electrolyte secondary battery according to any one of Configurations 9 to 11, wherein the ion conductive phase further comprises an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
[0140] Description of Reference Numerals
[0141] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer.
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing transition metal composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The sulfonic acid compound is a compound represented by formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, n is 1 or 2, The negative electrode comprises a carbon material and a silicon-containing material as negative electrode active materials, The content of the silicon-containing material is 3% by mass or less of the total mass of the negative electrode active material.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The sulfonic acid compound is present in an amount of 0.1 mass % or more and 1.0 mass % or less relative to the mass of the lithium-containing transition metal composite oxide.
3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: A in formula (I) is Li or Na.
4. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: R in the formula (I) is an alkyl group having 3 or less carbon atoms.
5. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The lithium-containing transition metal composite oxide has a layered rock salt structure.
6. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The initial charge and discharge efficiency of the negative electrode is above 90%. 7 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein the open circuit voltage of the positive electrode after discharging until the battery voltage reaches 2.5 V is lower than 3.555 V (vs. Li / Li+).
8. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.
9. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The silicon-containing material includes an ion-conducting phase, a Si phase dispersed in the ion-conducting phase, and a conductive layer covering a surface of the ion-conducting phase.
10. The nonaqueous electrolyte secondary battery according to claim 9, wherein The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.
11. The nonaqueous electrolyte secondary battery according to claim 9, wherein The ion conductive phase includes at least one selected from the group consisting of alkali metal elements and Group II elements.
12. The nonaqueous electrolyte secondary battery according to claim 11, wherein The ion conductive phase further contains an element M, and the element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A